A material and concept study of an enclosure to a fuel cell auxiliary power unit in marine applications - Stenvall, Erik (My University, 2010)
Powercell Sweden is developing fuel cell units as an alternative to combustion engines for power generation. This master project concerns a study of how these fuel cell units can be enclosed, used and installed in a boat. Important considerations for a fuel cell enclosure are for instance how to handle potential hydrogen leakages, how to ease serviceability and how to express and indicate the new technique provided by Powercell. These and many other considerations form the base to the developed and illustrated concept suggestions. One of the most important objectives in this project has been to investigate and suggest what materials and manufacturing methods that can be used for the enclosure of a fuel cell unit.
Keywords: Innovation och entreprenörskap (nyttiggörande); Materialvetenskap; Konstruktionsmaterial; Innovation & Entrepreneurship; Materials Science; Construction materials